Analisis Tarif Parkir di Kawasan Central Business DistrictT Kota Pangkalpinang - Revy Safitri (Universitas Mercu Buana, 2019)
Central Business District of Pangkalpinang, Plaza Pangkapinang – Bangka Trade Center Area, generate high vehicles trip. The high of vehicles trip that go to this area has created incerasing parking spaces requirement. One of the factors that influences in limiting parking spaces and as source of regional income is parking fee. So, the parking fee in Plaza Pangkalpinang – Bangka Trade Center Area needs to be analyzed to find out the suitablity of exsiting parking fee. In this research, analysis of parking fee was reviewed based on Ability To Pay (ATP) dan Willingness To Pay (WTP). The result of analysis shows that the parking fee of motorcycle for both on-street parking and parking lot, and the parking fee of car for on-street parking need to be adjusted with increasing parking facilities. While, the parking fee of car on parking lot has suited if followed by increasing parking facilities.